AD, Volume 23, n° 2, 1998 - Full Issue - Journal System (Africa Development, 1998)
Contents Les normes africaines en matière de protection de l'environnement, avec le Cameroun comme étude de cas Laurent Zang ......................................... 5 Food Policy: Managing Drought and the Environment in Botswana Kwaku Osei-H wedie ........................... 61 L'agriculture traditionnelle itinérante comme menace de l'environnement forestier: Quelles solutions Seka Pierre Roche ............................... 85 The Formulation and Implementation of Environmental Policy in Ghana Joseph R. A. Ayee ................................. 99 Building Regulatory Institutions in the Environmental Sector in the Third World: The Petroleum Inspectorate in Nigeria (1977-87) Eboe Hutchful ...................................... 121 Gendered Work Patterns in the Endangered Sahelian Rural Environment: Exploring Three Layers of Exploitation Abba Gana Shettirna ......................... 163 Les partis politiques et la démocratie au Mali Souleymane T. Koné ............................... 185 Traditional Versus Modern J udicial Practices: A Comparative Analysis of Dispute Resolution Among the South-West Yoruba of Nigeria Olukayode O. Taiwo .............................. 209 Ni meeting, ni défilé: Le syndicalisme de participation en Côte d'Ivoire a-t-il vécu? Ismaïla Touré .......................................... 227 Reviews Sustainable Development in Third World Countries: Applied and Theoretical Perspectives. Edited by Valentine Udoh James, Westport, Connecticut, Praeger, 1996, xvi + 245p. Paul Tiyambe Zeleza................................... 253 Dimensions of Development with Emphasis on Africa By Tekeste Negash and Lars Rudebeck, eds. Uppsala, Nordiska Afrikainstitutet and Forum for Development Studies, 1995, 279p. Paul Tiyambe Zeleza ................................. 257 Beingand Becoming Oromo: Historical and Anthropological Enquiries, By P. T. W. Bax.ter, Jan Hultin, and Alessandro Triulzi, eds., Uppsala, Nordiska Afrikainstitutet, 1996, 31Op. Paul Tiyambe Zeleza ............................... 261 Economie and Demographic Change in Africa, Edited by Archie Mafeje and Samir Radwan, Oxford, Clarendon Press, 1995, l 73p. Paul Tiyambc Zeleza ............................... 265